DARI JALANAN KE RING TINJU: TRANSFORMASI SOSIAL MELALUI FIGHT CLUB YOGYAKARTA: Transformasi Sosial Melalui Fight Club Yogyakarta - Maulana, Tesa (Fakultas Ushuludin Adab dan Humaniora Universitas Islam Negeri Prof. K.H. Saifuddin Zuhri, 2025)
Using the framework of Emile Durkheim's theory of social solidarity, this research analyzes the social transformation that occurred in the Yogyakarta Fight Club community in the context of local social problems. In Fight Club, the phenomenon of klitih, which indicates social dysfunction and mechanical solidarity, was successfully transferred to a more organized and systematic boxing activity. These activities lead to organic solidarity, where people from different backgrounds come together based on common goals and rules. Fight Club successfully brings back people who previously engaged in violent behavior into society by setting new, more constructive standards. Studies show that Fight Club Yogyakarta is not only a place to channel bad emotions, but also plays an important role in restoring social harmony.